Watching the weather - Eckart, Edana (New York Children's Press, 2004)
A simple introduction to how weather changes and how meteorologists forecast the weather
Warm weather -- A storm -- Studying weather -- New words
science (nature)
Includes bibliographical references (p. 23) and index
2
Keywords: Weather -- Juvenile literature; Weather